THE EFFECT OF PARAGRAPH HAMBURGER STRATEGY ON STUDENTS' ABILITY IN WRITING RECOUNT TEXT AT TENTH GRADE OF SMA NEGERI 1 SIANTAR - Hutagalung, Christina; Napitupulu, Selviana; Hutauruk, Bertaria Sohnata (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
This research was carried out to find out the effect of Paragraph Hamburger Strategy on students’ ability in writing recount text at tenth grade of SMA Negeri 1 Siantar. The research methodology used in this research was a quantitatve method with a quasi- experimental as a research design. The population of this research was tenth grade of SMA Negeri 1 Siantar in the academic year 2024/2025. The researcher took two classes as the sample. The samples were X-5 as experimental group consisted of 36 students and X-6 as control group consisted of 36 students. The experimental group was taught by Paragraph Hamburger strategy meanwhile control group was taught by Conventional strategy. The data were obtained by using pre-test and post-test given to both groups. The experimental class mean score on the pre-test was 66,5 and the mean score of control class was 68,02. On the other hand, the mean score of experimental class on pre-test was 77,30, while the mean score of control class on post-test was 74,88. To acquire data, the researcher used test as instrument. The result of t-test was 3,102 which was higher than t-table at 5% of level significance (1,667). The result of significance value indicates that alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected. It meant that there was significant effect by using Paragraph Hamburger strategy at tenth grade of SMA Negeri 1 Siantar in writing recount text.